Experiences from ten years of incident reporting in health care: a qualitative study among department managers and coordinators - Siw Carlfjord; Annica Öhrn; Anna Gunnarsson (BMC, 2018)
Abstract Background Incident reporting (IR) in health care has been advocated as a means to improve patient safety. The purpose of IR is to identify safety hazards and develop interventions to mitigate these hazards in order to reduce harm in health care. Using qualitative methods is a way to reveal how IR is used and perceived in health care practice. The aim of the present study was to explore the experiences of IR from two different perspectives, including heads of departments and IR coordinators, to better understand how they value the practice and their thoughts regarding future application. Methods Data collection was performed in Östergötland County, Sweden, where an electronic IR system was implemented in 2004, and the authorities explicitly have advocated IR from that date. A purposive sample of nine heads of departments from three hospitals were interviewed, and two focus group discussions with IR coordinators took place. Data were analysed using qualitative content analysis. Results Two main themes emerged from the data: "Incident reporting has come to stay" building on the categories entitled perceived advantages, observed changes and value of the IR system, and "Remaining challenges in incident reporting" including the categories entitled need for action, encouraged learning, continuous culture improvement, IR system development and proper use of IR. Conclusions After 10 years, the practice of IR is widely accepted in the selected setting. IR has helped to put patient safety on the agenda, and a cultural change towards no blame has been observed. The informants suggest an increased focus on action, and further development of the tools for reporting and handling incidents.